Stages of Learner Management in Secondary Schools - Azaria, Aura Rafa Hastin; Sekarningrum, Berliana; Zahra, Pande Made Natasha Lubna; Utami, Aulia Rahma; Zahra, Mahirah (Jurnal Inovasi Pembelajaran Karakter, 2025)
This article examines and elucidates the processes involved in managing students at secondary schools. This research employed a descriptive qualitative approach, utilizing interviews, observations, and additional documentation for data collection, which were then analyzed using an interactive model through reduction, expansion, and inference. The subjects of this study were the researcher, principal, director of academic affairs, and teaching staff. The study's findings reveal that the student affairs management process is conducted in collaboration with universities, with consideration given to their respective roles in managing student affairs.